Sex differences in the associations of water, coffee and tea consumption with cardiovascular diseases: a prospective cohort study - Ke, Dandan; Wang, Yueqing; Hou, Yabing; Shao, Weihao; Ke, Jiawen; Zhang, Xiaoxuan; Yang, Hongxi; He, Zhong; Lu, Zuolin (Frontiers in Nutrition, 2025)
BackgroundWater, coffee and tea are the primary sources of daily hydration. However, the sex-specific relationship between these beverages and cardiovascular disease (CVD) among remains unclear.MethodsIn total, 210,239 men and 251,383 women from the UK Biobank were included. The consumption of water, coffee and tea were self-reported. CVDs, including coronary heart disease (CHD), stroke and heart failure (HF) were followed till March 1st, 2023. Sex-specific Cox models were utilized to evaluate the hazard ratios (HRs) and 95% confidence intervals (CIs) for the associations.ResultsDuring a median follow-up of 8.7 years, 11,098 (2.40%) participants developed new-onset HF, 33,426 (7.24%) participants developed new-onset CHD, and 9,706 (2.10%) participants developed new-onset stroke. After adjustments, higher water consumption was generally associated with reduced risk of CVDs among both men and women. In contrast, heavy coffee consumption (particularly ≥6 cups/day) was associated with a greater risk of HF [1.16 (1.03–1.31) in men vs. 1.25 (1.12–1.40) in women], a greater risk of CHD [1.27 (1.18–1.36) in men vs. 1.21 (1.14–1.29) in women] and a greater risk of stroke [1.13 (0.99–1.29) in men vs. 1.20 (1.03–1.31) in women]. Similarly, heavy tea consumption was associated with an increased risk of HF (men: HR 1.19 [1.08–1.31]; women: HR 1.12 [1.02–1.23]) and CHD (men: HR 1.12 [1.05–1.18]; women: HR 1.18 [1.12–1.24]).ConclusionOur study revealed that water consumption was associated with a lower risk of CVDs, with a lower risk of CVDs, while heavy coffee or tea consumption was linked to a higher risk. Notably, coffee and tea consumption partially attenuated the protective association of water intake with CVDs. Furthermore, significant sex differences were observed in the associations between coffee or tea consumption and CHD incidence.